Correlates of psychological distress in penal and psychiatric populations - Biggam, Fiona Helen (1997)
This thesis is an investigation of social problem-solving skills, psychological distress, and supportive relationships among three distinct samples. The research groups comprise a) 25 depressed inpatients and a matched comparison group; b) 50 hospital admissions following an act of suicidal behaviour; and c) 5 sub-groups of incarcerated young offenders (inmates on Strict Suicidal Supervision, inmates on protection, victims of bullying, identified bullies, comparison group) with 25 inmates in each group. Data was collected by structured interviews, standardised psychometric measures of mood states (e.g. Hospital Anxiety and Depression Scale, Beck Hopelessness Scale), problem-solving ability (e.g. Means-Ends Problem-Solving Procedure) and supportive relationships (e.g. Significant Others Scale). Data were analysed by means of parametric statistical techniques (e.g. analyses of variance and multiple regression analyses). Eight cross-sectional studies are reported. Depressed patients demonstrated problem-solving difficulties, which were related to the level of psychological distress experienced. Clinically depressed patients were also found to differ from a comparison group in their autobiographical memory recall and concentration ability - both of which were related to their impoverished problem-solving ability. Deficits in problem-solving ability in the depressed patients were not an artefact of their verbal IQ. Regression analyses of the data relating to suicidal community inpatients illustrated that social support variables were the prime predictors of suicidal intent, depression and hopelessness. Social problem-solving variables also emerged as significant predictors of psychological distress, albeit to a lesser extent. Social support and problem-solving variables were also important moderator variables in the relationship between stress and suicidality. The studies conducted with young offenders illustrated a hierarchy of problem-solving deficits and psychological distress among the inmate groups. Problem-solving ability was not an artefact of verbal IQ. The value of using problem-solving interventions with vulnerable offenders is discussed. The importance of prison relationships in the experience of stress by inmates was also highlighted. Similarly, parental relationships were related to the levels of distress experienced while incarcerated. The results of each study are discussed in relation to the relevant literature, practical implications for clinical interventions with each group, and suggestions for future research. The findings of the thesis are discussed in relationship to transactional, stress-hopelessness-distress models of psychological illness and distress